A study on the mechanisms of teachers’ academic emotions and motivational beliefs on learning engagement in the context of online training - Zhang, Dongdong; Gao, Siyuan; Ren, Liling (Frontiers in Psychology, 2023)
In the context of digital transformation of education, online training is one of the important ways for teachers to improve their professionalism and promote the quality of education. However, studies have shown that teachers' online training suffers from insufficient learning engagement and other problems, so it is crucial to explore the factors influencing teachers' learning engagement and their mechanisms of action in the context of online training. Taking 589 teachers who participated in online training as the research subjects, the study used the methods of survey research and statistical analysis to explore the influence mechanism of teachers' academic emotions and motivational beliefs on online learning engagement based on the dual perspectives of control value theory and expectancy-value theory., and The study found that: (1) positive-high arousal academic emotions, training self-efficacy, and training task value significantly and positively predicted online learning engagement, respectively; (2) negative-high arousal and negative-low arousal academic emotions significantly and negatively predicted online learning engagement; (3) training self-efficacy and training task value mediated the relationship between positive-high arousal academic emotions, negative-high arousal academic emotions, negative-low arousal academic emotions and online learning engagement, respectively. The study concluded that by creating an immersive learning environment based on the educational meta universe, personalized and precise training based on big data and adaptive technologies, and establishing a multi-dimensional and three-dimensional online learning support service system, we which can effectively improve teachers' online learning engagement and enhance their online training quality and effectiveness.